A NARRATIVE INQUIRY ON HOW TEACHER PROFESSIONAL IDENTITY INFLUENCES TEACHER’S SCHOOL TYPE PREFERENCE - Rosari, Maria Dewi (LET: Linguistics, Literature and English Teaching Journal, 2019)
Some Indonesian English teachers prefer teaching in formal schools while some others favor non-formal schools more. This preference can be analyzed from the lense of teacher professional identity. In this study, the researcher tried to find out how teacher professional identity influences the school type teachers favor more. By conducting in-depth interviews to two non-formal school teachers from different regions in Indonesia, the researchers found out that job satisfaction, self-efficacy, occupational commitment, and occupational motivation are the factors influencing the participants? professional identity the most. Job satisfaction could be seen, for example, in witnessing students? progress more thoroughly; self-efficacy in being able to monitor their teaching performance; occupational commitment in teacher trainings provided by non-formal schools to build their career up; and occupational motivation in receiving manageable challenges from non-formal schools that trigger eagerness from the participants to work. Those findings could function as a reference for both formal and non-formal school stake holders in making sure that their schools could accommodate their teachers? need in constructing their professional identity as it could influence teachers? performance a lot.